Kyoto : - Mosher, Gouverneur (Charles E. Tuttle Co., 1964)
With this guide the visitor needs no further assistance to learn all that a place has to offer. It is factual, concise, and complete. This Japan travel book is generously illustrated with photographs, maps, route plans, and building plans, as well as a selection of reproductions from old prints and picture scrolls. The sights were specifically chosen to give foreign visitors a broad understanding of Kyoto's political, religious, and cultural history. Among them are the ancient Phoenix Hall of the Byodo-in, the famous rock garden at Ryoan-ji, the mountain temples of Enryaku-ji, the lavishly decorated Nijo Castle of the Tokugawas, the Silver Pavilion and its remarkable garden, and the "all-time temple,